OPTIMALIZATION OF GAS SUPERCRITIC IN EXTRACTING GAMMA-ORYZANOL FROM RICE BRAN - Maharani Patricia, Vinda
Rice bran is a by-product of rice milling process that have a wide range of pharmacological activity for its y-oryzanol compound. This study was aimed to optimize y-oryzanol extraction using gas supercritics and to determine its yorizanol content. y-Oryzanol extraction was done by modifying the pressure and temperature in order to obtain an optimum condition. The pressures used were 100 bar, 150 bar and 250 bar, while the temperatures used were 4000, 6000 and 8000. The were subsequently determined for their yield and the y-oryzanol contents were analyzed using thin layer chromatographic densitometer. An optimum condition used for extraction process to yield y-oryzanol crude extracts was a pressure of 250 bar at temperature 4000. By using the optimum condition, rice bran was extracted from red and black rice, and their y-oryzanol contents were determined. The y-oryzanol contents of rice bran from white, brown, and black rice were 0.92 ± 0.02, 1.23 ± 0.09, and 1.16 ± 0.045, respectively. Isolation ofy-oryzanol was performed through separation stages which were fractionation, subfractination, and purification by centrifugal thin layer chromatography, column classic chromatography, and preparative thin layer chromatography. Identification of yoryzanol by thin layer cromatography using authentic marker showed the isolate as y-oryzanol.